2013
DOI: 10.1111/jce.12210
|View full text |Cite
|
Sign up to set email alerts
|

Phrenic Nerve Injury: An Underrecognized and Potentially Preventable Complication of Pulmonary Vein Isolation Using a Wide‐Area Circumferential Ablation Approach

Abstract: High output pacing around the right pulmonary veins and the carina reveals that the phrenic nerve lies along a wide-area circumferential ablation trajectory in 30% of patients. Modification of ablation lines to avoid these sites may prevent phrenic nerve injury during RF PVI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“…These include limiting ablation to antral regions with various balloon maneuvers; preablation high-output pacing to establish whether the PN can be captured from the proposed ablation site before ablation; PN mapping with anatomic tagging of its course using an EAM system to guide the modification of the ablation lesion set; and monitoring of diaphragmatic excursion with abdominal palpation, fluoroscopy, or intracardiac ultrasound while pacing the PN from the SVC or subclavian vein during ablation. 1196 Monitoring the effects of pacing the right PN is now considered a standard part of CBA and should be considered during SVC isolation using RF energy. Of the writing group members, 96% report employing this technique when performing CB AF ablation.…”
Section: Section 10: Complicationsmentioning
confidence: 99%
“…These include limiting ablation to antral regions with various balloon maneuvers; preablation high-output pacing to establish whether the PN can be captured from the proposed ablation site before ablation; PN mapping with anatomic tagging of its course using an EAM system to guide the modification of the ablation lesion set; and monitoring of diaphragmatic excursion with abdominal palpation, fluoroscopy, or intracardiac ultrasound while pacing the PN from the SVC or subclavian vein during ablation. 1196 Monitoring the effects of pacing the right PN is now considered a standard part of CBA and should be considered during SVC isolation using RF energy. Of the writing group members, 96% report employing this technique when performing CB AF ablation.…”
Section: Section 10: Complicationsmentioning
confidence: 99%
“…Testing for PN capture was performed with high energy stimulation (20 mA at 2 ms pulse duration), with the ablation catheter along the anterior border of the right PVs (Fig. A,B).…”
Section: Methodsmentioning
confidence: 99%
“…It is more likely to occur with cryoballoon PVI than with radiofrequency (RF) energy. Recent studies demonstrated that PN injury can occur even when wide area circumferential ablation (WACA) approach is used . One possible explanation is the lack of an objective definition of WACA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,6 Furthermore, PN injury may persist in ≤33% of patients in long-term follow-up causing significant morbidity. 1,6 Several techniques for avoiding PN injury have been reported, including pace mapping to identify sites close to the PN to avoid ablation, 4,14 use of lower power settings (10 watts in one study), 15 and PN displacement using an epicardially placed balloon, sheath/catheter combination, and pericardial injection of saline, air, or both. 2,11,[16][17][18][19][20] The experience with PN displacement techniques is limited to animal studies, 19 isolated case reports, 2,11,16 or small series of patients.…”
mentioning
confidence: 99%